2014
DOI: 10.1038/jid.2013.303
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine Increases Matrix Metalloproteinase-1 and -3 Expression in Cultured Dermal Fibroblasts and Improves Scarring In Vivo

Abstract: We previously demonstrated that the formation of hypertrophic scarring on the wounds of a rabbit ear fibrotic model was significantly reduced by grafting a bilayer skin substitute expressing indoleamine 2,3-dioxygenase (IDO). Here, we hypothesize that the improved healing quality is due to extracellular matrix modulatory effect of IDO-mediated tryptophan metabolites. To test this hypothesis, a series of in vitro and in vivo experiments were conducted and the findings revealed a significant increase in the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 22 publications
6
57
0
Order By: Relevance
“…Our study showed that the expression of MMP-1 is increased 48 h after IPL irradiation [27]. Although it is well established that MMP expression was increased in damaged skin [28], some authors reported that the IPL management had no impact on MMP secretion levels in fibroblasts [29]. Some authors speculate that it could be an overlooked mechanism of skin rejuvenation, in which increased of MMP-1 will be implicated, contributing to the degradation of senescent collagens.…”
Section: Discussionmentioning
confidence: 54%
“…Our study showed that the expression of MMP-1 is increased 48 h after IPL irradiation [27]. Although it is well established that MMP expression was increased in damaged skin [28], some authors reported that the IPL management had no impact on MMP secretion levels in fibroblasts [29]. Some authors speculate that it could be an overlooked mechanism of skin rejuvenation, in which increased of MMP-1 will be implicated, contributing to the degradation of senescent collagens.…”
Section: Discussionmentioning
confidence: 54%
“…Chang et al (21) demonstrated that 5-aminolevulinic acid-based anti-HS photodynamic therapy induced increased expression of p53/p21 in HSFBs, which may further active the downstream molecules and promoted cell apoptosis. Furthermore, Li et al (22) observed that kynurenine treatment increased the expression of MEK and the phosphorylation of ERK1/2 in human dermal fibroblasts. He et al (23) also demonstrated the role of ERK signaling in loureirin B-induced inhibition of HS formation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these results suggest that KYN possesses properties that can be considered beneficial in the healing of the corneal epithelium. Indeed, there are reports showing that KYN can facilitate and modulate healing processes [7, 11, 36]. Interestingly, wounds that received IDO genetically modified dermal fibroblasts healed more quickly than those of the controls [7].…”
Section: Discussionmentioning
confidence: 99%
“…KYN markedly suppresses the expression of collagen types I and III while increasing the expression of matrix metalloproteinase-1 and matrix metalloproteinase-3 in dermal fibroblasts [7]. Anti-scarring properties of KYN were also demonstrated in a fibrotic rabbit skin ear wound model in vivo [36]. On the other hand, it was suggested that the upregulation of the KYN pathway, independent of glucose metabolism, may play an important role in the progression of diabetes-induced fibrosis in the corneal stroma and may contribute to corneal scarring and delayed wound healing [43].…”
Section: Discussionmentioning
confidence: 99%